Storytelling for Cyberbullying Prevention in Adolescents: A Literature Review. - Günal, Büşra Dağcı; Alkaya, Sultan Ayaz (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2026)
With the rapid advancement of digitalization, adolescents’ social interactions have increasingly shifted to online environments. Adolescence is a developmental period characterized by intensified peer influence, identity formation, and high levels of social media engagement, all of which may increase vulnerability to involvement in cyberbullying. In this context, cyberbullying is widely recognized as a significant public health concern. Research indicates that low levels of empathy constitute one of the key psychological factors contributing to cyberbullying behaviors. Accordingly, interventions aimed at enhancing empathy have emerged as prominent preventive strategies. Storytelling is an effective method for fostering empathy, as it enables individuals to experience the events from diverse perspectives and assume different roles. In recent years, school-based interventions incorporating storytelling have been shown to reduce cyberbullying behaviors and enhance empathy levels. In this regard, school health nurses—beyond their role in individual counseling—are well positioned to implement story-based interventions through group education programs and the development of school policies. Accordingly, this review summarizes the literature and provides recommendations tailored to adolescents and school settings, with particular emphasis on the role of school nurses in coordinating storytelling-based prevention strategies.